Some issues on the observance of continuity and interdisciplinary relations in teaching humanities subjects - Rajeckas, V. (Psichologija, 1968)
Application of continuity principle and interdisciplinary relations facilitates fuller, deeper and more versatile understanding of taught subjects and bears considerable significance in development of communist awareness. N. Krupskaya paid major attention to interdisciplinary subjects.The article contains concrete examples specifying how writers’ lives and creative work should be analyzed, how Russian literature should be studied in Lithuanian school and provides generalized conclusions. Major attention is also paid to inclusion of the fiction works in History lessons and possibilities of application of such means are revealed.Some results of the experimental work enable to maintain that application of the principles of continuity and interdisciplinary relations is a vital condition to increase the effectiveness of a lesson.
Keywords: interdisciplinary relations; continuity; teaching of humanities subjects